Effects of diets containing linseed oil on fatty acid desaturation and oxidation in hepatocytes and intestinal enterocytes in Atlantic salmon (Salmo salar) - Tocher, Douglas R; Fonseca-Madrigal, Jorge; Bell, J Gordon; Dick, James R; Henderson, R James; Sargent, John R (Springer, 2002)
We hypothesized that replacing fish oil with 18:3n-3-rich linseed oil may enable salmon to maintain the levels of tissue n-3HUFA levels through a combination of increased desaturation activity and increased substrate fatty acid provision. To this end we investigated desaturation/elongation of [1-14C18:3n-3 in hepatocytes and intestinal enterocytes, and determined the extent to which 18:3n-3 was oxidized and desaturated by measuring both simultaneously in a combined assay. Salmon smolts were stocked randomly into five seawater pens and fed for 40 weeks on diets in which the fish oil was replaced in a graded manner by linseed oil. At the end of the trial, fatty acyl desaturation/elongation and oxidation activities were determined in isolated hepatocytes and intestinal enterocytes using [1-14C]18:3n-3 as substrate, and samples of liver and intestinal tissue were collected for analysis of lipid and fatty acid composition. The results showed that, despite increased desaturation of [1-14C]18:3n-3 in hepatocytes, provision of dietary 18:3n-3 did not prevent the decrease in tissue n-3HUFA in fish fed linseed oil. Intestinal enterocytes were a site of significant fatty acid desaturation but, in contrast to hepatocytes, the activity was not increased by feeding linseed oil and was generally lower in fish fed linseed oil compared to fish fed only fish oil. In contrast, oxidation of [1-14C]18:3n-3 in enterocytes was generally increased in fish fed linseed oil compared to fish fed the diet containing only fish oil. However, oxidation of [1-14C]18:3n-3 in hepatocytes was 4- to 8-fold lower than in enterocytes and was not affected by diet. Furthermore, oxidation of [1-14C]18:3n-3 in enterocytes exceeded desaturation irrespective of dietary treatment, whereas similar amounts of [1-14C]18:3n-3 were desaturated and oxidized in hepatocytes from fish fed only fish oil and desaturation exceeded oxidation by 3-fold in fish fed the diet containing 100% linseed oil. The molecular mechanisms underpinning these results were discussed.